Effects of chloropicrin fumigation combined with biochar on soil bacterial and fungal communities and Fusarium oxysporum - Jiahong Zhu; Aocheng Cao; Jiajia Wu; Wensheng Fang; Bin Huang; Dongdong Yan; Qiuxia Wang; Yuan Li (Ecotoxicology and Environmental Safety, 2021)
Chloropicrin (CP) can cause long-term damage to beneficial microbes which reduces soil health. Biochar (BC) can mitigate against the effects of CP by reducing the time for beneficial microbes to recover after CP fumigation. In this study, we used Real-Time Quantitative PCR to determine the effects of different rates of BC added to CP-fumigated soil on the speed of recovery of bacteria and fungi population and on changes to gene copy number of the target pathogen Fusarium oxysporum. And then we compared the structure and composition of the beneficial microbial community in the different treatments soil by using High throughput Illumina sequencing. As the results shown, adding 1 or 3% BC after CP fumigation accelerated the recovery of bacterial and fungal populations without increasing F. oxysporum abundance. BC also promoted the recovery of beneficial bacteria Rokubacteria and Latescibacteria damaged by CP. And these two bacteria may be related to the immunity of soil to F. oxysporum. In CP-fumigated soil, BC improved the disease resistance of the soil by increasing beneficial microbes, such as Steroidobacter, Sphingomonas, Purpureocillium and Mortierella. This combination of CP and BC is a new concept that could encourages the development of a healthy and sustainable soil ecosystems while controlling plant pathogens.